Removal of Toxic Metal Ions from Aqueous Solutions in Integrated Clay Adsorption and Electroflotation - Raimundo Nonato Pereira Teixeira; Vicente Oliveira Sousa Neto; Juliene Tomé Oliveira; Lucas Fontenele Amorim; Eliezer Fares Abdala Neto; Diego de Quadros Melo; Henrique Douglas Melo Coutinho; Bonglee Kim; Jorge Marcell Coelho Menezes; Ronaldo Ferreira do Nascimento (Adsorption Science & Technology)
Most galvanic process industries treat their effluents by chemical precipitation methods. Such a method produces an amount of galvanic sludge that is often disposed of inappropriately to the environment, causing major environmental damage. These rejects present high concentrations of toxic metallic ions, such as copper (Cu(II)), lead (Pb(II)), nickel (Ni(II)), and cadmium (Cd(II)). Several alternatives have been proposed to contribute in a cheaper and efficient way to treat these effluents. This study aimed to describe the results obtained in the removal of the concentrations of Cu(II), Ni(II), Cd(II), and Pb(II) ions, present in an aqueous solution, by the use of a hybrid system combining the adsorption and electroflotation processes simultaneously. The adsorbent materials used were two Brazilian soil clays classified as sodium clay (SC) and ferric clay (FC). For the electroflotation process, aluminum, iron, and stainless-steel electrodes were used. The obtained data showed good efficiency in the removal of the four metallic ion concentrations. The best results presented a reduction in the concentration of Cu(II), Ni(II), Cd(II), and Pb(II) ions of 50.11%, 36.71%, 21.59%, and 23.43%, respectively, when it was used the hybrid system formed by the ferrous clay as adsorbent and the aluminum electrode for the electroflotation process.